Students' perceptions of choice criteria in the selection of tertiary institutions: A regional comparison - Ghazali, Zahiruddin; Mohamad, Mohamad Hanapi (Palgrave Macmillan, 2003)
The issue of tertiary institution choice criteria has without doubt been widely researched.This is due to intense competition for full fee-paying foreign students in tertiary education.The identification of the criteria considered important to future customers is a prerequisite for the development of strategies, especially at a time when Malaysia has projected the image of being a centre of excellence in education.This chapter examines regional differences in current customer choice criteria.A questionnaire containing four factors with 19 variables was used in a sample of 721 foreign students to gain insight into Malaysian tertiary education and develop relevant strategies.